2021
DOI: 10.3389/fmicb.2021.763289
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Monitoring of Mycobacterium leprae Infection in Nine Banded Armadillos (Dasypus novemcinctus) Using a Quantitative Rapid Test

Abstract: Leprosy is an infectious disease caused by Mycobacterium leprae with tropism for skin and peripheral nerves. Incessant transmission in endemic areas is still impeding elimination of leprosy. Although detection of M. leprae infection remains a challenge in asymptomatic individuals, the presence of antibodies specific for phenolglycolipid-I (PGL-I) correlate with bacterial load. Therefore, serosurveillance utilizing field-friendly tests detecting anti-PGL-I antibodies, can be applied to identify those who may tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…We have previously shown that antibody levels for the M. leprae-specific PGL-1 correlate with bacterial load in armadillos (39)(40)(41). In order to determine the correlation between anti-PGL-1 antibody levels and impaired nerve conduction, we stratified 71 M. leprae-infected armadillos at different stages of leprosy disease into two groups according to serum anti-PGL-1 IgM antibody levels.…”
Section: Correlation Of Mnct With Disease Progression and Anti-pgl-1 ...mentioning
confidence: 99%
“…We have previously shown that antibody levels for the M. leprae-specific PGL-1 correlate with bacterial load in armadillos (39)(40)(41). In order to determine the correlation between anti-PGL-1 antibody levels and impaired nerve conduction, we stratified 71 M. leprae-infected armadillos at different stages of leprosy disease into two groups according to serum anti-PGL-1 IgM antibody levels.…”
Section: Correlation Of Mnct With Disease Progression and Anti-pgl-1 ...mentioning
confidence: 99%
“…Over the past years, we have developed a robust, user-friendly test that detects anti-PGL-I IgM antibodies using the unique upconverting reporter particle (UCP) technology in a low-cost lateral flow-based assay (LFA) format [( 18 , 22 26 ) and Pierneef et al ( manuscript in preparation )]. The anti-PGL-I UCP-LFA offers a sensitive, low-complexity rapid test to quantitatively determine anti-PGL-I IgM levels in capillary and venous blood ( 24 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that zoonotic transmission is possible from a nine‐banded Armadillo ( Dasypus novemcinctus ) to healthy individuals 3 . Leprosy is not an inherited disorder, but genetics and the alteration in genes may increase susceptibility towards the disease.…”
Section: Introductionmentioning
confidence: 99%